2001
DOI: 10.1128/aac.45.6.1682-1687.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Modeling of the Electroencephalogram Effect of Imipenem in Healthy Rats

Abstract: A pharmacokinetic-pharmacodynamic (PK-PD) modeling approach was developed to investigate the epileptogenic activity of imipenem in rats. Initially, animals received an intravenous infusion of imipenem at a rate of 2.65 mg min ؊1 for 30 min. Blood samples were collected for drug assay, and an electroencephalogram (EEG) was recorded during infusion and postinfusion. A dramatic delay was observed between concentrations of imipenem in serum and the EEG effect; this effect was accompanied by tremors and partial sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…IPM analysis. Analysis of IPM in the dialysates was performed by an adaptation of a previously described HPLC assay (11,12,24). Standard curves were prepared with IPM in water at concentrations ranging from 0.78 to 50 g · ml Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
“…IPM analysis. Analysis of IPM in the dialysates was performed by an adaptation of a previously described HPLC assay (11,12,24). Standard curves were prepared with IPM in water at concentrations ranging from 0.78 to 50 g · ml Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
“…We have recently developed an experimental approach using quantitative electroencephalogram (EEG) recording together with pharmacokinetic-pharmacodynamic (PK-PD) modeling to characterize the epileptogenic activity of imipenem in rats (9). This investigation led to the conclusion that there was no simple direct relationship between the antibiotic's concentration in plasma and its EEG effect.…”
mentioning
confidence: 99%
“…However, the present study was conducted with Sprague-Dawley rats receiving norfloxacin at 150 mg/kg of body weight compared to Wistar rats treated with 300 mg/kg of norfloxacin in the previous experiment (10), which could partially explain this apparent discrepancy. The difficulty of finding doses appropriate for the inducement of reversible and therefore nonlethal seizures but sufficiently severe to have an effect on the EEG signal was previously mentioned (2,5). Preliminary tests suggested that a 300 mg/kg dose of norfloxacin was too high for the present study, and the 150 mg/kg dose was considered a better compromise.…”
mentioning
confidence: 93%
“…The goodness of fit of each model was assessed by visual inspection and analysis of the residuals and of the percentage of the coefficient of variation associated to parameter estimates (2,5). Two control animals underwent the same experimental protocol except that norfloxacin administration was replaced by isotonic saline administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation